IMPLEMENTASI MANAJEMEN PERUBAHAN DI MAN 3 PALEMBANG SUMATERA SELATAN - Afriantoni Afriantoni (Ta'dib: Jurnal Pendidikan Islam, 2014)
Madrasah Aliyah Negeri (MAN) 3 Palembang is unique enough to be studied because since inception of Islamic religion teacher education institutions. The results of this study found that type of leadership visoner is owned by head of Man 3 Palembang oriented management of change and continues over time. Visionary leadership is the key. Head of MAN 3 Palembang has been able to create, formulate, communicate, socialize, transform, and implement the ideal thoughts coming from him and the result of social interaction between members of organization and stakeholders that are believed to achieve ideals of organization in the future. In addition, management of change has been initiated through an internal analysis of the organization by identifying four areas, namely services, finance, human resources and facilities in order to discover the strengths and weaknesses internal to the organization. All of this has been the commitment of all personnel MAN 3 Palembang to achieve my goals and success. Lastly, head of MAN 3 Palembang has been able to implement management changes, so that the organization built quality improvement-oriented leadership, teacher quality, school programs, students' final exam results, student achievement and strong school culture.